Documenting and Explaining the Dramatic Rise of the New Society Journals in Economics - John C. Ham; Julian Wright; Ziqiu Ye (Institute of Labor Economics (IZA), 2023)
An important recent event in the economics field is the introduction of seven new society journals. Using standard iterative ranking methodologies from economics, as well as some new methodologies, we demonstrate the spectacular rise of these journals while updating journal rankings for all economics journals. We then use regression analysis based on how these journals and natural comparison journals are cited in top-5 economics journals to investigate the roles of editor reputation, editor experience, bias from parent journals, the number of articles published, as well as other factors in explaining the new journals' strong relative performance.
Keywords: A11; C23; C81; J44; 330; impact factors; academic associations; journal ranking